ANALYSIS OF THE EFFECT OF PARTICIPATION, TRANSPARENCY AND ACCOUNTABILITY ON THE MANAGEMENT OF VILLAGE FUND ALLOCATION IN BANUA HANYAR HULU VILLAGE, TAPIN UTARA DISTRICT, TAPIN REGENCY, SOUTH KALIMANTAN PROVINCE - Dwi Nanda Mahdenny; Musthafa, Musthafa (Sean Institute, 2022)
This research is a correlational research with a quantitative approach through a survey method which aims to determine the effect of participation, transparency and accountability on the management of the Banua Hanyar Hulu Village Fund, Tapin , Tapin Regency, either simultaneously or partially. This study also wants to determine whether participation is a dominant factor in Village Fund Management. With the number of samples in this study as many as 90 respondents with the determination of the sample using purposive sampling technique. Data collection techniques by distributing questionnaires and documentation. While the instrument uses validity and reliability tests. Furthermore, the data were analyzed using a statistical model in a computer program (SPSS version 23) using the classical assumption test and multiple linear regression analysis testing. The results of this study indicate that simultaneously, the independent variables, namely Participation, Transparency and Accountability, can affect the Management of the Banua Hanyar Hulu Village Fund, Tapin, Tapin Regency. While partially, only the transparency variable cannot affect the Management of the Banua Hanyar Hulu Village Fund, Tapin, Tapin Regency. This study also found that the dominant influence on the management of the Banua Hanyar Hulu Village Fund, Tapin, Tapin Regency is the accountability variable.